Evaluation of real driving emissions with acting regulations (3rd and 4th RDE packages) in Korea - Soo Yu, Young; Soo Chon, Mun; Cha, Junepyo (Alexandria engineering journal, 2022)
The European Union (EU) introduced the real driving emission (RDE)-LDV management system in September 2017, and it has been studying its implementation to ensure consistency with established regulations. This study investigated NOx emissions and applied different after-treatment methods in the new European driving cycle (NEDC) and world-wide harmonized light-duty vehicles test cycle (WLTC) modes on 25 test vehicles. In addition, this study was conducted on the KOR-route, which satisfies the RDE-LDV regulations. This study aims to compare and analyze the results of the evaluation methods of the 3rd and 4th RDE packages using data measured from 25 test vehicles after employing different after-treatments. The results indicated that vehicles with an LNT system satisfied the NOx emission limit (0.08 g/km) in the NEDC mode; however, it was more than 2.5 times over the NOx emission limits in the WLTC mode. In addition, vehicles with an SCR system satisfied the NOx emission limit in both modes. Compared to the evaluation methods of the 3rd and 4th RDE packages, the slope of the complete RDE trip was close to 1, and the slope of the urban part of the RDE trip was measured as 0.94. The first parameter of the function used to calculate the first parameter of the result evaluation factor (RFL1) changed to 1.3 after January 2020. The RDE-NOx emission value was higher than that measured before; this was because of the RDE result evaluation factors, which were affected by the first parameter of the function used to calculate the increase in the result evaluation factor.